a + b + 2a - b + 3a + 5b = 6a + 5b
2x + 3y - 2z + 3z - 2x - 3y = z
2x - 1 + 3x - 2 - 4x - 6 + 1 + 4z = x - 8 + 4z
4a - 5 - 5a + 4 + 2a + 1 - 3a = -2a
x - 4y + 1 - x + 3y - 4 + 3x - y + 5 = -2y + 2 + 3x
-5a + bc - 2ab + 4bc + 5a + 4bc + 2ab = 9bc
m + n - 2m + 3n - 8 - m + 6n = 10n - 2m - 8
10x^2y - 5xy^2 - 8x^2y + 2x^2y = 4x^2y - 5xy^2
8x - 4x + 6y - 5 - 5y + 8x - 2 = 12x + y - 7
2a + b - 3a + 6b - 1 + a + 4b = 11b - 1
-x^2 - 2xy - xy - 2x^2 + 4 + 3xy - x^2 = -4x^2 + 4
-3a - 6a - 4b - 5a + 5b - 2a + 3b = -16a + 4b
-6x - 4y - 6x + 2y + 3x - y - 4x + 12 + 10y = -13x + 7y + 12
-8x - 2 - 4xy + 8xy - 10 - 2x + 6x = -4x - 12 + 4xy